The Materiality of the Digital: Form of Archive from Hardware to Interface - Giacomazzi, Marco (E|C, 2023)
The article examines the pervasiveness of digital technologies, the remediation of traditional media, and the emergence of a new set of practices, actors, knowledge, and languages that are based on an apparently virtual space but are deeply rooted in computer networks, program codes, and material servers. The importance of a material approach to meaning-making in the digital context will be emphasized, with a focus on the interaction with media technologies. It argues that the impression of immateriality associated with digital technologies is not simply a reconfiguration of the tangibility of traditional media but rather a reorganization of the semiotic agency generated by digital media technology itself. The article underscores the need to consider the significance of material signs and the associated agency, along with the reintroduction of epistemological principles from the semiotics of technical objects. The Material Engagement Theory highlights the importance of interaction as a participatory moment in the emergence of meaning. Based on these theoretical assumptions, the objective is to establish the foundations for a semiotics of media technologies that avoids technological determinism.